Historical cost vs. Fair value and their influence on earnings’ quality - Benzerrouk, Zakia Said; Esawi, Khaldah Abdalla; Shehab, Lamia Ismael (Journal of Economic, Administrative and Legal Sciences, 2023)
The controversy has increased recently between supporters of the historical cost model and supporters of the fair value model as a basis for measurement in accounting, by comparing the priorities of the characteristics that should be available in the accounting information. Since the accuracy and validity of this information depends on the validity, appropriateness, and reliability of the measurement alternatives on which it was based to access this information. In this research, we will address the two accounting alternatives, the historical cost, and the fair value, and compare the impact of each on the quality of profits in the Jordanian banking sector. The historical cost that represents the actual reality of the event at the time of its occurrence at the moment of exchange is undoubtedly correct or accurate at the moment of acquisition or ownership, but the recorded value may become a thing of the past as it deviates slightly or a lot from the current value. The results of the field study indicated that fair value provides information that is highly suitable for decision-making and is comparable to accounting information in the Jordanian banking sector.